ANALISIS MUTU PRODUK COOKIES BERBASIS JANTUNG PISANG SEBAGAI ALTERNATIF MAKANAN SELINGAN IBU MENYUSUI - Aulia, Arsy; Sulaeman, Agus; Dewi, Maryati; Fitria, Mona (Poltekkes Kemenkes Bandung, 2022)
Low production of breast milk in breastfeeding mothers is one of the factors causing the low coverage of exclusive breastfeeding in infants. One of the efforts to increase breast milk production is to provide food lactogenic formula. Indonesia has many local foodstuffs that can help facilitate breast milk production, one of which is the banana heart. Banana heart-based cookies are a form of food product development to improve product quality as an alternative food interlude for breastfeeding mothers rich in flavonoids. This study aims to determine the effect of wheat flour and banana heart flour formulations on organoleptic properties and total flavonoid levels. The research was experimental using a Complete Random Design (CRD) one factor; the balance of wheat flour and banana heart flour 25%:75%, 50%:50%, and 75%:25%. The quality testing of cookies was conducted by a hedonic test conducted by 30 trained panelists. The UV-Vis Spectrophotometric method analyzed the total flavonoid levels with AlCl3 reagents. The results showed an influence of the balance of wheat flour and banana heart flour on the taste, texture, and overall cookies (p<0.05). The most preferred cookies by panelists are cookies with wheat flour formula and banana heart flour 75%:25%. One serving of cookies is 52 grams or as many as four pieces. The total content of flavonoid cookies is based on the test results on the most preferred products at 36.92 ppm. Further research is needed to determine the effect of giving cookies on the production of breast milk intended as a snack for breastfeeding mothers.